Spousal support and subjective career success : the role of work-family balance and career commitment as mediator - Amin, Shofia; Rasidah Arshad,; Rohayu Abdul Ghani, (Penerbit Universiti Kebangsaan Malaysia, 2017)
The present study aims to investigate the antecedent of career success from work-family perspective. Specifically, it examines both direct relationship between spousal support and subjective career success, and indirect relationship via work-family balance and career commitment. Data were collected using survey method from four hundred and seventeen nurses working in hospitals in Jambi, Indonesia. To test the hypotheses, Structural Equation Modeling (SEM) statistical technique was employed. The results of the study indicate that spousal support is positively related to career success. Work-family balance was found to mediate the relationship between spousal support and subjective career success, while career commitment was found to mediate the relationship between work-family balance and subjective career success. The study bridges the work-family research and career success research area, and brings together the literature on role theory, spillover theory, conservation of resources theory in one model.